The microstratigraphic record of human activities and formation processes at the Mesolithic shell midden of Poças de São Bento (Sado Valley, Portugal) - Duarte, Carlos (2018)
Shell midden formation is largely controlled by an-thropogenic processes, resulting from human exploitation of aquatic resources. This makes shell middens archives of bothhuman behaviour and palaeoenvironmental records.However, their often complex stratigraphy hampers the isola-tion of individual anthropogenic events. In the central/ southern coast of Portugal, extensive inland estuaries were preferential settings for Mesolithic groups from c. 6200 calBC. Here, we present a microstratigraphic approach to theshell midden of Poças de São Bento, one of the largest and best-knownsitesintheSadoValley.Themicrofaciesapproachwas based on sedimentary components, their abundance andarrangement, and post-depositional processes. Anthropogenic processes identified as tossing events and anthropogenicallyreworked deposits allowed inferences on spatial organisation, preferential refuse areas, occupational surfaces, and temporal-ity of the occupations. The presence of calcareous pebbles inthe anthropogenic, shell-rich sediments, together with forami-nifera, presumably from the estuarine marshes, is compared with the regional geology, providing a hypothetical location of the shellfish gathering. The microstratigraphy described reveals a full internal dynamic in the formation of the apparently homogeneous shell midden layer. The human activities inferred at Poças de São Bento have many similarities with those reported for Cabeço da Amoreira in the nearby Tagus palaeo-estuary. This evidence points to the need for further micro-morphological approaches in similar deposits. The study of shell midden formation processes, through integrative microcontextual approaches, plays a major role in understanding Mesolithic societies in the large early Holocene estuary environments of Atlantic Iberia.